(F)utility of "routine" postprocedural chest radiograph after hemodialysis catheter (central venous catheter) insertion. Issue 1 (January 2021) - Parmar, Malvinder S
A routine postprocedural chest radiograph had been a safe, checklist-based final step of the procedure, since the start of central venous catheter insertion for hemodialysis to check the position of the catheter tip and to rule out complications. However, the chest radiograph is a suboptimal method to rule out complications like pneumothorax and is not a reliable test to confirm its position. Although it is relatively inexpensive, it is labor-intensive and exposes patient to unnecessary radiation exposure, cost, and often results in delayed use of the catheter. Various studies question the value of a routine chest radiograph as a screening test to rule out the mechanical complications of catheter insertion. We, in this brief viewpoint, present evidence to support the futility of a routine postprocedural chest radiograph in majority of asymptomatic patients and support Choosing Wisely Initiative to avoid low-value studies. However, it should be considered under specific indications, as discussed.